STRATEGI KOMUNIKASI PEMASARAN SOSIAL PERPUSTAKAAN NASIONAL DALAM PROSES PUBLIKASI DIGITAL KHASTARA UNTUK MENJADI BRAND HERITAGE - Sadewa, Puspanagri Mas Bayu; Tomasowa, Gloria Angelita (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
This study aims to analyze the social marketing communication strategy implemented by the National Library of Indonesia in publicizing the digitalization of the Khastara collection as part of its efforts to establish its identity as a brand heritage. The method used in this study is descriptive qualitative, with data collection techniques through in-depth interviews, observations, and documentation studies of Khastara publication activities across various communication channels. The results show that an educational, persuasive, and participatory communication approach is key to building public awareness of the historical and cultural values contained in the Khastara collection. This strategy is packaged through social media, official websites, and digital literacy campaigns targeting the younger generation and the academic community. The heritage brand identity is formed through visual and verbal narratives that emphasize the uniqueness and authentic value of the Khastara collection as a national heritage. Thus, a structured and integrated social marketing communication strategy plays a significant role in strengthening the National Library's position as an institution preserving the nation's collective memory through the digitization of its collections. This study recommends the development of more adaptive and sustainable cultural messages to expand the reach and impact of Khastara's digital publications.